Interaktif ve Karmaşık Mimari Sistemler Üzerinden Toleransı Yeniden Düşünmek - Delerel, Zehra; Tan Bayram, Funda (İstanbul Teknik Üniversitesi, 2025)
Bu çalışma, mimarlıkta tolerans kavramını hesaplamalı tasarım bağlamında yeniden tanımlayarak, onu yalnızca üretim hatalarına karşı bırakılan teknik bir pay olmaktan çıkarıp; değişkenlik, etkileşim ve bağlamsal duyarlılık temelinde üretken bir tasarım stratejisine dönüştürmektedir. Tarihsel olarak kesinlik ve kontrolle ilişkilendirilen tolerans, burada sistem davranışı yoluyla açık uçlu mekânsal senaryolar üretme kapasitesine sahip etkin bir parametre olarak ele alınmaktadır (Kolarevic, 2014). Bu dönüşümü araştırmak amacıyla, Rhino 3D ortamında interaktif duvarlar üreten, karmaşık iki özel Python scripti geliştirilmiştir. Her iki script, çekim noktalarına (attractor) tepki veren çift yüzeyli sistemler üretmekte; yüzey geometrileri ekstrüzyon ve açıklık değerleri üzerinden farklılaşmaktadır. Bu değişkenler, tolerans kavramının hesaplanabilir biçimde yeniden tanımlanmasını sağlamaktadır. Ortak parametrelerle çalışan modeller, tepki mantıkları açısından farklılık gösterir: Kod 1 yüzeyler arasında karşıtlık ve gerilim oluşturarak kontrast temelli bir mekânsal deneyim üretirken; Kod 2, senkronize ve geçirgen yapısıyla süreklilik ve birlik hissi sunmaktadır. Karşılaştırmalı analiz, toleransın parametrik sistemlerde yalnızca biçimsel değil, aynı zamanda davranışsal bir çerçeve olarak da işlev gördüğünü ortaya koymuştur. Her iki model, zamansal değişkenlik üzerinden gündelik yaşamın karmaşıklığını simüle eden etkileşimli senaryolar geliştirmektedir. Sonuç olarak, çalışma toleransı, algoritmik kontrol ile gerçek dünya belirsizlikleri arasında köprü kuran üretken ve performatif bir tasarım aracı olarak yeniden konumlandırmakta; mimari yüzeyleri optimize edilmiş formlar yerine sürekli dönüşen, yaşayan kompleks sistemler haline getirmektedir.

This study reconsiders the concept of tolerance within the context of computational design, repositioning it not merely as a margin for error in production processes, but as an interactive, contextual, and uncertainty-driven design strategy. Historically associated with engineering precision, tolerance has evolved in computational design environments into a framework that embraces variability, system-level adaptability, and behavioral diversity (Kolarevic, 2014). Rather than pursuing precision as an end goal, this shift enables tolerance to function as a generative principle within dynamic systems. Within this framework, the aim of the research is to model tolerance as a reconfigurable design parameter that enables interactive spatial variation, and to rethink architectural surfaces in accordance with this variability. The study involves the development of two custom Python scripts within the Rhino 3D environment, which generate dual-wall parametric systems responsive to attractor points. These surfaces are topologically differentiated through extrusion and aperture values, and each unit is semantically encoded via a four-bit logic system—translating spatial behavior into computationally readable data. The comparative structure of Code 1 and Code 2 reveals how systemic responses transform design strategies. Code 1 produces oppositional reactions to attractors, generating spatial contrast between the walls. This design logic aligns with Venturi’s (2005) proposition that contrast and imperfection serve as sources of architectural meaning. In contrast, Code 2 synchronizes the behavior of both surfaces: as they move away from the attractors, their extrusion values increase uniformly. This behavior resonates with Moloney’s (2009) notion of kinetic systems, offering a model in which coordinated transformation replaces static form. Both scripts illustrate how tolerance can function not only as a technical allowance but as an adaptive, behavioral, and interactive parameter embedded within system logic. While Code 1 generates spatial tension through contrasting wall responses, Code 2 produces a porous, unified field of interaction. McVicar’s (2016) definition of tolerance as a “range of opportunity” is embodied here through the ability of the same input to yield divergent spatial outcomes. Additionally, the micro-variations embedded into each unit allow for dynamic feedback responses that echo Wiener’s (2019) cybernetic models. In conclusion, this study reframes tolerance as a productive variable within parametric modeling, capable of mediating between computational control and real-world complexity. The surface variations generated by the scripts move beyond fixed geometries, creating dynamic spatial scenarios informed by data and context. In doing so, the concept of tolerance becomes not a constraint to be minimized, but a mechanism for enabling open-ended, temporally evolving design systems. Ultimately, this research contributes to a broader understanding of computational design by proposing a model in which uncertainty, interaction, and systemic adaptability become core architectural values. By encoding tolerance as a formal and behavioral operator, the study opens new avenues for designing data-rich, responsive, and performative environments. This approach positions architectural surfaces not as endpoints of optimization, but as active participants within complex, living systems of spatial negotiation.
Rethinking Tolerance through Interactive and Complex Architectural Systems
Keywords: Computational Complexity and Computability; Hesaplama Karmaşıklığı ve Hesaplanabilirlik; Architectural Computing and Visualisation Methods; Mimari Bilgi İşlem ve Görselleştirme Yöntemleri; Architectural Design; Mimari Tasarım